Determination of a shear rate threshold for thrombus formation in intracranial aneurysms. (27th July 2015) - Ribeiro de Sousa, Daniel; Vallecilla, Carolina; Chodzynski, Kamil; Corredor Jerez, Ricardo; Malaspinas, Orestis; Eker, Omer Faruk; Ouared, Rafik; Vanhamme, Luc; Legrand, Alexandre; Chopard, Bastien; Courbebaisse, Guy; Zouaoui Boudjeltia, Karim
Abstract : Background: Particular intra-aneurysmal blood flow conditions, created naturally by the growth of an aneurysm or induced artificially by implantation of a flow diverter stent (FDS), can potentiate intra-aneurysmal thrombosis. The aim of this study was to identify hemodynamic indicators, relevant to this process, which could be used as a prediction of the success of a preventive endovascular treatment. Method: A cross sectional study on 21 patients was carried out to investigate the possible association between intra-aneurysmal spontaneous thrombus volume and the dome to neck aspect ratio (AR) of the aneurysm. The mechanistic link between these two parameters was further investigated through a Fourier analysis of the intra-aneurysmal shear rate (SR) obtained by computational fluid dynamics (CFD). This analysis was first applied to 10 additional patients (4 with and 6 without spontaneous thrombosis) and later to 3 patients whose intracranial aneurysms only thrombosed after FDS implantation. Results: The cross sectional study revealed an association between intra-aneurysmal spontaneous thrombus volume and the AR of the aneurysm (R 2 =0.67, p<0.001). Fourier analysis revealed that in cases where thrombosis occurred, the SR harmonics 0, 1, and 2 were always less than 25/s, 10/s, and 5/s, respectively, and always greater than these values where spontaneous thrombosis was not observed. Conclusions: Our study suggests the existence of an SR threshold below which thrombosis will occur. Therefore, by analyzing the SR on patient specific data with CFD techniques, it may be potentially possible to predict whether or the intra-aneurysmal flow conditions, after FDS implantation, will become prothrombotic.